ANALYSIS OF AFFIX –LY AS MODIFIER OF ADVERB OF MANNER IN SOCIAL MEDIA POSTS : ANALISIS IMBUHAN –LY SEBAGAI PEWATAS ADVERBIA KECARAAN DALAM KIRIMAN MEDIA SOSIAL - Irwan Suswandi (Jurnal Kata, 2022)
This analytical descriptive research aims to describe a linguistic phenomenon that is popular among social media users, namely the use of the suffix –ly in Indonesian vocabulary. The approaches used were morphological, syntactic, and semantic. The data collection method chosen was the note-taking method with data analyis technique used distributional method. The data collected were 12 sentence data containing the words anggunly, jujurly, barbarly. Based on the results of the analysis, morphologically, the affix –ly in the words anggunly, jujurly, barbarly is a suffix that must be tied to the base morpheme that is classified as an adjective. Syntactically, the affix –ly changes the base morpheme that is classified as an adjective into an adverb. Semantically, the affix –ly has the same meaning as the modifier of the adverb in Indonesian, namely ‘secara’ and ‘dengan’. The emergence of the affix –ly as the modifier of adverb is the result of language contact with English and is increasingly being popularized by an influencer, Vindy Lee, so that it becomes slang language.